Vacuum polarization of generalized quantum electrodynamics in the Heisenberg picture - Montenegro, David [UNESP] (World Scientific Publishing, 2020)
In this work, we consider the generalized quantum electrodynamics proposed by Podolsky in Heisenberg picture via Källén methodology. We investigate the effects of higher-order derivatives to understand the qualitative and quantitative aspects of vacuum polarization. In addition, the most general structure of induced current and polarization tensor that emerge naturally by a perturbative scheme à la Källén is also obtained. Afterward, we discuss the physical implication of charge renormalization in the perspective of unitary and stable Podolsky theory.
Keywords: Heisenberg picture; Källén; no-mixing gauge; Podolsky electrodynamics; vacuum polarization